Adaptive strategies and sustainable investments: navigating organizations through a VUCA environment in and after COVID-19 - Minciu, Mihaela; Veith, Cristina; Dobrea, Razvan Catalin; Ionescu, Vladimir-Codrin (Technological and Economic Development of Economy, 2025)
This study delves into the resilience and adaptability of employees within the volatile, uncertain, complex, and ambiguous (VUCA) business environment, examining their readiness to manage effectively and the organizational agility in navigating change, alongside the impact of sustainable investment practices. Employing quantitative methods, a survey was conducted among employees at two pivotal moments: during and after the COVID-19 pandemic restrictions. Factorial analysis revealed a strong preference for participatory work styles and highlighted the critical need for employee involvement in significant decision-making processes. Although the value of sustainable investments was recognized, a noticeable gap was found in employees’ understanding and adaptability towards these investments. The use of the Wilcoxon test illuminated the significant impact of external disruptions, such as the pandemic, on organizational operations and preparedness. The findings underscore the imperative for organizations to champion continuous learning and training, enabling strategic and innovative responses to the challenges unique to the VUCA world. By aligning adaptive interventions with the demands of the VUCA environment, organizations can define a clear trajectory towards sustainable growth and enhance their proactive stance against sudden shifts in the business landscape. First published online 10 September 2024